EFEKTIVITAS MEDIA PEMBELAJARAN INTERAKTIF BERBASIS APLIKASI FLASH CS6 TERHADAP KEMAMPUAN BERPIKIR TINGKAT TINGGI PADA MATERI SISTEM KOPLING - Ratu Okta, Yang; Arif Budiman , Febrian; Wahyudi, Wahyudi; Iskandar, Ranu (Penerbit Lafadz Jaya, 2025)
This study aims to examine the effectiveness of interactive learning media based on Flash CS6 in improving students’ Higher Order Thinking Skills (HOTS) on the clutch system material for grade XI TKR students at SMK Perintis 29 Ungaran. The research employed a quantitative approach using a quasi-experimental design with a Nonequivalent Control Group Pretest-Posttest Design. Instruments used include HOTS test items, student response questionnaires, and expert validation sheets. The validation results indicated that the media was highly feasible, scoring 94.5% from media experts and 98% from subject matter experts. Learning outcomes showed that the experimental class experienced a significantly higher improvement than the control class. The N-Gain score for the experimental group was 76.8% (effective category), while the control group was only 49.2% (less effective category). The t-test revealed a significant difference between the posttest scores of both groups (p < 0.05). Furthermore, student responses to the media were very positive, with an average score of 88.2%. These results suggest that Flash CS6-based interactive learning media is effective in enhancing students’ HOTS, particularly in vocational education related to light vehicle engineering subjects.